Cryobiopsy as a reliable technique for the preoperative identification of micropapillary/solid components in early-stage lung adenocarcinoma. (December 2021) - Suzuki, Mikito; Matsumoto, Yuji; Imabayashi, Tatsuya; Teishikata, Takashi; Tsuchida, Takaaki; Asamura, Hisao; Yatabe, Yasushi
Highlights: MIP and SOL subtypes are associated with poor prognosis. Preoperative identification of MIP/SOL components help decide the treatment plan. Cryobiopsy can collect larger tissue samples with less crush artifacts. Concordance is higher for primary or secondary predominant patterns. Cryobiopsy reliably identifies MIP/SOL components in early-stage lung adenocarcinoma. Abstract: Objectives: Micropapillary (MIP) and solid (SOL) subtypes of early-stage lung adenocarcinomas are associated with lymph node metastasis and local recurrence after limited resection. Preoperative identification of these components may influence the decisions of treatment strategy, additional lymph node evaluation, indication for limited resection, and extent of lymph node dissection. However, conventional biopsy specimens are insufficient for identifying these subtypes, especially MIP components. Cryobiopsy can collect larger tissue samples with fewer crush artifacts than conventional forceps biopsy, which would be helpful for detecting MIP/SOL components. Thus, this study aimed to analyze the feasibility of using cryobiopsy for MIP/SOL subtype detection. Material and methods: Consecutive patients who underwent surgery for clinical IA lung cancer following a preoperative diagnosis of adenocarcinoma by cryobiopsy at our institution between October 2017 and July 2019 were retrospectively examined. The concordance rate of MIP/SOL subtypes between the specimens obtained by cryobiopsy and surgery was investigated. Results: In total, 115 patients were evaluated. There were 26 (22.6%) and 14 (12.2%) patients with MIP and SOL subtypes, respectively. For concordance of MIP/SOL subtypes, the sensitivity was 65.7% (95% confidence interval [CI]: 57.7–65.7%). For the primary or secondary predominant patterns, a more satisfactory concordance rate of 72.2% (95% CI: 52.6–86.2%) was obtained. On assessing each subtype, high sensitivity was noted in SOL-predominant patterns (85.7%, 95% CI: 56.5%–96.0%) and MIP-secondary predominant patterns (83.3%, 95% CI: 45.8–97.0%). However, SOL-secondary predominant patterns revealed low sensitivity (0%, 95% CI, 0–38.2%). Overall, the MIP subtypes had higher sensitivity than the SOL subtypes (65.4% vs. 50.0%). Conclusion: Cryobiopsy could be reliable for identifying MIP/SOL components, especially the MIP component, in clinical stage IA adenocarcinomas.